Conversion of carbon dioxide into fuels—A review. (August 2022) - Okoye-Chine, Chike George; Otun, Kabir; Shiba, Nothando; Rashama, Charles; Ugwu, Samson Nnaemeka; Onyeaka, Helen; Okeke, Chinedu T.
Abstract: The continuous rise in the quantity of CO2 emissions in the atmosphere and the threat it poses to humankind and its environment are issues of great concern to everyone in the world. Also, the declining fossil fuel reserves are an issue of worry considering the increasing demand for energy globally. Therefore, the conversion of CO2 into fuels is a promising and convenient way to minimize global warming caused by the growing concentration of CO2 in the atmosphere and meet the world's high energy demand. The conversion of CO2 into fuels is achieved via various chemical conversion and biological conversion methods. The progress and development made so far in producing environmentally friendly alternative fuels from the conversion of CO2 boost the industrialization of sustainable fuel production. However, the conversion of CO2 into fuels via chemical conversion and biological conversion methods are plagued with some challenges. This article focused on the recent advances, problems, and prospects for future research regarding the conversion of CO2 into fuels. Highlights: The conversion of CO2 into fuels is a promising way to minimize global warming and increase energy demand. Evaluation of various chemical and biological conversion methods used to convert CO2 to fuels. Limitations of the different chemical and biological conversion methods used to convert CO2 to fuels. Opportunities for future research regarding the conversion of CO2 into fuels.